Exploring placement stability for children in out-of-home care in England: a sequence analysis of longitudinal administrative data. (November 2020) - Mc Grath-Lone, Louise; Harron, Katie; Dearden, Lorraine; Gilbert, Ruth
Abstract: Background: To monitor stability of care, the proportion of children in England who have experienced three or more placements in the preceding 12-month period is published in government statistics. However, these annual snapshots cannot capture the complexity and heterogeneity of children's longitudinal care histories. Objective: To describe the stability of care histories from birth to age 18 for children in England using a national administrative social care dataset, the Children Looked After return (CLA). Participants and setting: We analyzed CLA data for a large, representative sample of children born between 1992 and 1994 ( N = 16, 000). Methods: Using sequence analysis methods, we identified distinct patterns of stability, based on the number, duration, and timing of care placements throughout childhood. Results: Although care histories were varied, six distinct patterns of stability were evident including; adolescent 1 st entries (17.6%), long-term complex care (13.1%) and early intervention (6.9%). Overall, most children (58.4%) had a care history that we classified as shorter term care with an average of 276 days and 2.48 placements in care throughout childhood. Few children (4.0%) had a care history that could be described as long-term stable care. Conclusions: Longitudinal analyses of administrative data can refine our understanding of how out-of-home care is used as a social care intervention. Sequence analysis is a particularly useful tool for exploring heterogeneous and complex care histories. Considering out-of-home care histories from a life course perspective over the entire childhood period could enable service providers to better understand and address the needs of looked after children.